2010
DOI: 10.1088/0953-8984/22/39/395403
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics simulation of the martensitic phase transformation in NiAl alloys

Abstract: Using molecular dynamics simulations with an embedded-atom interatomic potential, we study the effect of chemical composition and uniaxial mechanical stresses on the martensitic phase transformation in Ni-rich NiAl alloys. The martensitic phase has a tetragonal crystal structure and can contain multiple twins arranged in domains and plates. The transformation is reversible and is characterized by a significant temperature hysteresis. The magnitude of the hysteresis depends on the chemical composition and stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 18 publications
2
10
0
Order By: Relevance
“…We attribute the large theoretical hysteresis to (1) the absence of heterogeneous nucleation sites such as defects and (2) the prevention of active habit planes as the size of the simulation cell is tiny compared to that of experimental samples. The importance of heterogeneous nucleation sites was reported in previous MD simulations on the phase transition of a NiAl shapememory alloy [84][85][86][87][88]. These works also resulted in a large thermal hysteresis (≈1000 K) if simulations were started using defect-free crystals, in accordance with our present finding.…”
Section: B Temperature-induced Phase Transition Of Pure Tisupporting
confidence: 92%
See 1 more Smart Citation
“…We attribute the large theoretical hysteresis to (1) the absence of heterogeneous nucleation sites such as defects and (2) the prevention of active habit planes as the size of the simulation cell is tiny compared to that of experimental samples. The importance of heterogeneous nucleation sites was reported in previous MD simulations on the phase transition of a NiAl shapememory alloy [84][85][86][87][88]. These works also resulted in a large thermal hysteresis (≈1000 K) if simulations were started using defect-free crystals, in accordance with our present finding.…”
Section: B Temperature-induced Phase Transition Of Pure Tisupporting
confidence: 92%
“…These works also resulted in a large thermal hysteresis (≈1000 K) if simulations were started using defect-free crystals, in accordance with our present finding. Further simulations considering various kinds of defects, such as a dislocation [85], a grain boundary [84,88], an antiphase boundary [85], and a free surface [85,86], confirmed that such defects can significantly reduce the thermal hysteresis window. Figure 11(a) also illustrates the occurrence of a solid-liquid phase transition upon continued heating of the solid phase to higher temperatures.…”
Section: B Temperature-induced Phase Transition Of Pure Timentioning
confidence: 84%
“…To demonstrate the ability of the new Ni-Al-Co potential to reproduce the martensitic phase transformation, a series of atomistic simulations was conducted for various chemical compositions. In the previous study of the binary Ni-Al system [15], the austenitic phase was first equilibrated at temperature of 1200 K by semi-grand canonical Monte Carlo simulations to create an equilibrium state of long-and short-range order. The austenite was then subject to cooling and heating cycles by molecular dynamics (MD) simulations to observe the martensitic transformation.…”
Section: Simulation Methods and Modelsmentioning
confidence: 99%
“…The martensitic phase was found to contain multiple twins arranged in domains and plates, with crystallographic characteristics consistent with experimental observations. This study [15] utilized an embedded-atom method (EAM) potential [16] that had been constructed by adopting previously developed Ni [17] and Al [18] potentials and fitting the cross-interaction function to a database of first-principles and experimental data. The ability of this potential to correctly reproduce the thermodynamics and crystallography of the martensitic phase transformation in the binary Ni-Al system was demonstrated in [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation